Dissecting the Position of Living Law in the Criminal Code 2023 - Andini, Orin Gusta (Trunojoyo Madura University, 2024)
This study analyzes the position of living law in the 2023 Criminal Code. Through normative research methods using a legislative approach and a conceptual approach, this article finds: First, the position of living law in the 2023 Criminal Code is narrowed down to only referring to customary law as regulated in the explanation of Article 2. Second, the regulation of customary law is a recognition of sanctions for fulfilling customary obligations that will be used by judges as guidelines for sentencing. Third, the living law sanction in the 2023 Criminal Code is a type of additional criminal sanction in the form of fulfilling local customary obligations. Violations of the provisions of living law are subject to principal criminal sanctions and additional criminal sanctions if the act has been regulated by the 2023 Criminal Code. The regulation of additional criminal sanctions in the form of customary obligations aims to accommodate the types of customary law sanctions. In addition, there is a substitution mechanism for perpetrators who cannot fulfill customary obligations, in the form of substitution of compensation whose value is equivalent to a category II fine to a supervision sentence or social work sentence.